Soil CO₂ efflux under different plantation types and its association with chronosequence factor - Sigau, Cindy Usun (2017)
Impacts of land use modifications from anthropogenic activities towards soil CO₂ efflux are still poorly understood and varies between sites. Therefore, soil CO₂ efflux in three mature plots of Gmelina arborea and Swietenia macrophylla (exotic broad-leaved trees) and Pinus caribaea (an exotic conifer) was studied in relation to soil, air temperature and relative humidity on a monthly basis from January to March of 2016. Soil properties including bulk density, pH, total C, total N, and soil organic carbon were also measured at depth of 0–15 and 15–30 cm. Soil CO₂ efflux was recorded to be significantly different between the plots: gmelina (0.76 ± 0.04 g CO₂ m-2 h-1) > mahogany (0.49 ± 0.02 g CO₂ m-2 h-1) > conifer (0.40 ± 0.01 g CO₂ m-2 h-1). Regression analysis revealed a significant positive correlation between soil CO₂ efflux and temperature in the gmelina plot. There was no significant correlation noted between soil CO₂ efflux and relative humidity in all the three plots. A significant negative correlation was found between soil CO₂ efflux and temperature in the conifer plot, indicating the influence of other factors on soil CO₂ efflux in the plot. Comparing the broadleaved gmelina and needle-leaved pine, monthly variations in soil relative humidity and soil properties were examined for possible influences on soil CO₂ efflux and temperature sensitivity (Q10) in the plots. Temperature sensitivity of soil CO₂ efflux in the gmelina plot (Q10 = 1.19) was significantly higher than that of mahogany and pine plots (Q10 = 0.79 and 0.70 respectively). The findings also showed significant result in the chronosequence in oil palm and rubber plantations which influence the soil CO2 efflux. Twenty-two years old plantation stands (0.91 ± 0.17 g CO₂ m-2 h-1) had significantly higher soil CO₂ efflux than 6 years old plantation stands (0.54 ± 0.18 g CO₂ m-2 h-1). These findings suggest the chronosequence factor influenced the variations of soil CO₂ efflux in tropical oil palm and rubber plantations, driven significantly by soil relative humidity. The overall significant difference in soil CO₂ efflux was associated with the changes in land structure leading to the evolution in soil respiration variations, especially in the morphological and the physiological aspects. In addition, major environmental influences on soil CO₂ efflux were soil temperature and soil relative humidity, which reacted differently in different plantation types and age stands. Thus, emphasizing how land use management can affect soil CO₂ efflux significantly by altering the environmental responses accordingly.